2020
DOI: 10.1371/journal.ppat.1008621
|View full text |Cite
|
Sign up to set email alerts
|

CD11cHi monocyte-derived macrophages are a major cellular compartment infected by Mycobacterium tuberculosis

Abstract: During tuberculosis, lung myeloid cells have two opposing roles: they are an intracellular niche occupied by Mycobacterium tuberculosis, and they restrict bacterial replication. Lung myeloid cells from mice infected with yellow-fluorescent protein expressing M. tuberculosis were analyzed by flow cytometry and transcriptional profiling to identify the cell types infected and their response to infection. CD14, CD38, and Abca1 were expressed more highly by infected alveolar macrophages and CD11c Hi monocyte-deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
93
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(125 citation statements)
references
References 68 publications
20
93
3
Order By: Relevance
“…Consistent with this observation, we found that expression of CD11c correlated inversely with both bacterial stress (hspx9::GFP) and drug tolerance, which indicates that CD11c + IMs are permissive for Mtb growth. The identification of a CD11c + , Mtb-infected IM population both in our study and that of Lee et al (2020) raises the possibility that recruited, monocyte-derived macrophages can also give rise to a subpopulation of permissive host phagocytes capable of supporting bacterial expansion and disease progression.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Consistent with this observation, we found that expression of CD11c correlated inversely with both bacterial stress (hspx9::GFP) and drug tolerance, which indicates that CD11c + IMs are permissive for Mtb growth. The identification of a CD11c + , Mtb-infected IM population both in our study and that of Lee et al (2020) raises the possibility that recruited, monocyte-derived macrophages can also give rise to a subpopulation of permissive host phagocytes capable of supporting bacterial expansion and disease progression.…”
Section: Discussionsupporting
confidence: 52%
“…To date, CD11c and SiglecF have been used as ontogenic markers to separate AMs from IMs. Recently, this notion has been challenged by the identification of a population of Mtb-infected monocyte-derived macrophages that are CD11c high (Lee et al, 2020). Using ADT staining, we reclustered the infected cells based on the expression of surface markers rather than transcriptional profile.…”
Section: Expression Of the Surface Marker Cd11c Is Inversely Associated With Drug-tolerant Bacteriamentioning
confidence: 99%
“…In separate studies with 8 mice per treatment group from 3 independent studies and following mouse euthanasia and lung perfusion, lungs were inflated with 1 ml digestion solution/mouse containing 0.5 mg/ml Liberase TM [17][18][19][20].…”
Section: Lung Cell Sortingmentioning
confidence: 99%
“…The distinct capabilities of these populations in controlling Mtb growth have emerged recently in studies using a mouse model (Huang et al 2018). Resident alveolar macrophages present a permissive environment for Mtb growth (Huang et al 2018) and decrease in numbers during the course of infection (Lee et al 2020). Whereas, interstitial macrophages, derived from blood monocytes, accumulate in lungs, exhibit a Th1-like celltype and restrict bacterial growth (Huang et al 2018).…”
Section: Introductionmentioning
confidence: 99%